Swoistość ludzkiej kultury - wampiryzm - Jacek Tomczyk; Anna Dygudaj (Studia Ecologiae et Bioethicae)
Every myth, regardless of its nature, refers back to some event placed in illio tempore. By this fact it constitutes a pattern to all situations and activities in which the event may reappear, the myth can degrade into an epical legend, a ballad or a roman, but it can also survive in a limited form in superstitions, customs and longings without losing neither its structure nor its meaning. In the history of mankind, the perception contributed to the formation of culture - the total of artifacts, both material and immaterial (spiritual or symbolic), these achievements, characteristic for particular society, constitute a model of social behavior. While interpreting the external world people relied on supernatural explanations to some extent, which depended on the level of intellectual development. Initially many facts were explained with the interference of dark, demonic powers, adopting diverse forms in people’s imagination, thanks to such interpretation of reality the vampire was born to existence.